Methods of International Services Trade Statistical Recording - Vengrauskas, Petras Vytautas; Langvinienė, Neringa (Ekonomika, 2003)
There are presented suggestions of article authors for development of Lithuanian international trade of services statistical recording. And essential criteria for sample size selection for statistical information collection, criteria for data collection according to special groups and variables for statistical information estimation there are, too. Besides that opportunity to develop a statistical registration in Lithuania at the end of article you will find, too.